1998
DOI: 10.1093/jac/42.6.689
|View full text |Cite
|
Sign up to set email alerts
|

Class I integrons in Gram-negative isolates from different European hospitals and association with decreased susceptibility to multiple antibiotic compounds

Abstract: Class I integrons are associated with carriage of genes encoding resistance to antibiotics. Expression of inserted resistance genes within these structures can be poor and, as such, the clinical relevance in terms of the effect of integron carriage on susceptibility has not been investigated. Of 163 unrelated Gram-negative isolates randomly selected from the intensive care and surgical units of 14 different hospitals in nine European countries, 43.0% (70/163) of isolates were shown to be integron-positive, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
171
7
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(208 citation statements)
references
References 20 publications
22
171
7
8
Order By: Relevance
“…Other reports have shown the prevalence of class 1 integrons in gram-negative clinical isolates to be c. 43% in Western and Central Europe [8], .50% in the Netherlands [20] and 59% in France [7]. Among aminoglycoside-resistant isolates from the USA, nearly 75% had integrons [11].…”
Section: Discussionmentioning
confidence: 96%
“…Other reports have shown the prevalence of class 1 integrons in gram-negative clinical isolates to be c. 43% in Western and Central Europe [8], .50% in the Netherlands [20] and 59% in France [7]. Among aminoglycoside-resistant isolates from the USA, nearly 75% had integrons [11].…”
Section: Discussionmentioning
confidence: 96%
“…Regarded as a primary source of antimicrobial resistance genes and reservoirs and exchanging platforms of resistance genes within microbial populations, the role of class 1 integron in the dissemination of antibiotic resistance genes had been well investigated and documented in a large number of gram-negative bacteria (Labbate et al, 2009;Maguire et al, 2001;Martinez-Freijo et al, 1998;Sallen et al, 1995). Nevertheless, investigations on Gram-positive bacteria still remained limited.…”
Section: Class 1 Integronmentioning
confidence: 99%
“…Integrons are natural expression vectors that permit the insertion of antibiotic resistance genes by a site-specific recombinational mechanism. Only a few studies suggested that integrons are widespread in both animal and human clinical bacterial isolates [6][7][8][9]. The purpose of this current study was to determine the incidence of integrons from E. coli isolates obtained from some selected animals in Republic of Korea.…”
Section: Introductionmentioning
confidence: 99%